Mathématiques
clemence0301
30

Pouvez-vous m'aider à factoriser - merci d'avance A= x²-4+4 B= 9x² +12x+4 C=(2x+1)²-(2x-1)² D= (5x-1)(3x+1)+(5x-1)² E = (3x+1)(2x-3)+(2-3x) F= (5x-15)(7-x)+(x-3)(2x+1) G= (4-2x)(3x-1)+(x-2)(1-5x) H= (x-2)(6x-4)+ 9x²-12x+4 I= (x+2)(3x+2)-2x-1 Merci beaucoup

+3
(1) Réponses
rayantebari

A=x²-4x+4=(x-2)²B=9x²+12x+4=(3x+2)²C=(2x+1)²-(2x-1)²=[(2x+1)-(2x-1)][(2x+1)+(2x-1)]=(2x+1-2x+1)(2x+1+2x-1)=2*2x=8xD=(5x-1)(3x+1)+(5x-1)²=(5x-1)(3x+1+5x-1)=(5x-1)*8x=8x(5x-1)E=(3x+1)(2x-3)+(2x-3)=(2x-3)(3x+1+1)=(2x-3)(3x+2)ou E=(3x+1)(2-3x)+(2-3x)=(2-3x)(3x+1+1)=(2-3x)(3x+2)F=(5x-15)(7-x)+(x-3)(2x+1)=5(x-3)(7-x)+(x-3)(2x+1)=(x-3)(35-5x+2x+1)=(x-3)(-3x+36)=3(x-3)(-x+12)G=(4-2x)(3x-1)+(x-2)(1-5x)=-2(x-2)(3x-1)+(x-2)(1-5x)=(x-2)(-6x+2+1-5x)=(x-2)(-11x+3)H=(x-2)(6x-4)+9x²-12x+4=2(x-2)(3x-2)+(3x-2)²=(3x-2)(2x-4+3x-2)=(3x-2)(5x-6)I=(x+2)(3x+2)-2x-1=(x+2)(3x+2)-(2x+1)

Ajouter une réponse